Blinding clues: unveiling the ocular manifestations of preeclampsia - Thanigachalam, Kunthavvai; N., Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Preeclampsia is a hypertensive disorder of pregnancy that significantly contributes to maternal and fetal morbidity and mortality. Although its hallmark manifestations include hypertension and proteinuria, systemic complications affecting various organs, including the ocular system, are often under-recognized. Ocular manifestations range from mild visual disturbances to severe complications such as cortical blindness and retinal detachment. These complications reflect the systemic endothelial dysfunction and vascular permeability characteristic of preeclampsia. Early recognition of ocular symptoms can serve as a valuable indicator of disease severity and progression, prompting timely intervention. In this case, a 37-year-old gravida 2, para 1, at 30+6 weeks of gestation presented with severe hypertension (200/110 mm Hg), headache, and loss of vision. A diagnosis of posterior reversible encephalopathy syndrome (PRES) was suggested, likely secondary to cerebral edema associated with preeclampsia. The patient underwent emergency lower-segment caesarean section (LSCS) after stabilization with intravenous Labetalol and magnesium sulphate (MgSO4). Postoperatively, her visual symptoms resolved within six hours, and an ophthalmological evaluation revealed a normal fundus examination. This case shows the importance of recognizing preeclampsia-induced ocular changes, as timely intervention can prevent irreversible complications such as optic neuropathy and permanent vision loss. Multidisciplinary management, including obstetric and ophthalmologic care, is critical to achieving favorable maternal and fetal outcomes. Routine monitoring and ophthalmological evaluations in high-risk pregnancies are essential to early detection and effective management. This case highlights the reversible nature of preeclampsia-induced ocular complications and emphasizes the role of expedited delivery in mitigating severe outcomes.